2011
DOI: 10.1177/0363546511420079
|View full text |Cite
|
Sign up to set email alerts
|

Medial Patellofemoral Ligament Reconstruction With a Divergent Patellar Transverse 2-Tunnel Technique

Abstract: The results of modified MPFL reconstructions are encouraging, with minimal risks of redislocation and an overall patient satisfaction rate of over 80%. These early and medium-term results are comparable with those of other MPFL reconstruction techniques reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
147
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 66 publications
5
147
0
1
Order By: Relevance
“…Nevertheless suture anchor fixation may be sufficient when compared with the native MPFL. Panni et al 20 , in the 45 patients undergoing reconstruction of the MPFL, had an increase of the main evaluation scales (Kujala from 56.7 pre-operatively to 86.8, Lysholm from 57.6 pre-operatively to 88.1) and reported the presence of one of the most dangerous complications in reconstruction the MPFL, the fracture of the patella. Christiansen et al 21 , in 44 subjects investigated with MPFL reconstruction, showed an increase of Kujala score from 46 pre-operatively to 84, presenting four episodes of dislocation after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless suture anchor fixation may be sufficient when compared with the native MPFL. Panni et al 20 , in the 45 patients undergoing reconstruction of the MPFL, had an increase of the main evaluation scales (Kujala from 56.7 pre-operatively to 86.8, Lysholm from 57.6 pre-operatively to 88.1) and reported the presence of one of the most dangerous complications in reconstruction the MPFL, the fracture of the patella. Christiansen et al 21 , in 44 subjects investigated with MPFL reconstruction, showed an increase of Kujala score from 46 pre-operatively to 84, presenting four episodes of dislocation after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical results are good and the re-dislocation rate is low [3,5,8,15,18,23,24,32]. Kohn et al [15] examined 42 patients 2 years after MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…_ 2 ) T D $ F I G ] Among all the different double-bundled MPFL reconstruction procedures described in the literature so far, majority of them vary in the methods of patellar fixation, which can be categorised into looping though bone-tunnels [24][25][26], partial bone drilling with aperture interference screw fixation with interference [27][28][29][30], and patellar rim fixation with suture anchors [31][32][33][34]. Among them, we believe patellar rim fixation with suture anchors theoretically offers the most advantages than the bone-tunnel and interference screw fixation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The 3.5-mm metal anchor used in this technique was found to have a pull-out strength of 295 N in a porcine model [37], in comparison, the pull-out strength of interference screw fixation in the setting of MPFL reconstruction have yielded slightly inferior results, with through-tunnel fixation failing at 195 N and aperture fixation failing at between 126 and 241 N [35,38]. Second, patellar fractures, the most serious complication after double-bundled MPFL reconstruction, have been reported only in procedures with patellar-bone tunnel fixation [24,28,29,39], for bone tunnels may act as stress risers whereas suture anchor fixation, sparing of bone drilling, such complication may be minimised. In a systematic review of complications after MPFL reconstruction, Shah et al [40] reported a trend of more overall complications observed utilising the bone-tunnel techniques (29.8%) compared with the sutureanchor techniques (21.6%).…”
Section: Discussionmentioning
confidence: 99%